Dynamic capabilities: axiomatic formation of firms’ competitive competencies - Mushangai, Dandira (Elsevier, 2023)
The capabilities concept is critical in understanding the competitive competencies of firms. Capabilities allow firms to sense, seize and reconfigure their resources in response to opportunities and threats within their environments. This systematic review reviewed a total of 37 Scopus database-selected peer-reviewed articles on capabilities, technology, innovation, and capability frameworks. The purpose was to identify and discuss firms’ capabilities and formation processes and effects on competitive advantages to generate an encompassing framework that overcomes the limited and fragmented nature of current capability frameworks. The study employed thematic content analysis and author-anchored keywords analysis which enabled the identification of several themes regarding capabilities and formation processes. The findings of the study were discussed under the following themes: technological capabilities; supply chain capabilities; networking, collaboration, interactive, coordinating, and alignment capabilities; organisational capabilities; and lastly systems capabilities. The study contributes to enlightening a body of firms’ capabilities theories and generated an encompassing interactive capabilities framework to guide researchers in understanding firms’ capabilities formation processes. The value of the study to the research community lies in emphasising the multi-level approach (macro; mezzo; firm level) and the virtues of combining tenets from different frameworks for a nuanced understanding of firms’ capabilities development. The study will be critical in guiding firms in building their capabilities, particularly the importance of open innovation networks and collaboration in reducing innovation risks and costs. The paper is important to policy makers regarding the institutions facilitating the interaction of international, national and firms level dynamics in propping and propelling firms’ capabilities development.
Keywords: Capabilities; Technology; Competitive advantage; Innovation; Framework; SDG-17: Partnerships for the goals